Gaya Bahasa dan Makna dalam Iklan Produk Glico pada Channel Youtube Glico Japan - Trahutami, S.S., M. Hum, Sri Wahyu Istana -; Trahutami, S.S., M. Hum, Sri Wahyu Istana (KIRYOKU, 2024)
This paper will study the comparison between of Language Style and Meaning in Glico Product Advertisements on the Glico Japan YouTube Channel." This research aims to: 1) To describe the language style used in advertisements on the Glico Japan YouTube Channel; 2) Describe the meanings contained in advertisements on the Glico Japan YouTube Channel. The research data were obtained from twenty-six Glico advertisements found on the Glico Japan YouTube channel. The data collection method in this thesis was simak method with catat technique. Then, using pilah unsur penentu to analyze the data. Meanwhile, informal method is used to presenting the results of the analysis. Based on the results of the analysis, it can be concluded that there are 16 instances of repetition language style; simile; metaphor; personification; hyperbole; and inversions. Meanwhile, for meanings, there are conceptual meanings, affective meanings, and connotative meanings.